INDIANA JONES REFLECTED AS A AMERICAN CHARACTER IN THE INDIANA JONES AND THE RAIDERS OF THE LOST ARK. (TRANSFORMATION FROM POPULAR NOVEL INTO MOVIE) - Ardian, Edi (Islamic University of Indragiri, 2017)
Literature represent of the certain society. Literature includes poem, prose, and drama. Nowadays, Movie is one of pop-literature that was developing. Many work of art that made into movie in order to of the message to public easily. One of work of art that transform from poplit into movie is the Indiana Jones and the raiders of the Lost Ark. The character that presented by the Indiana Jones represented of the American culture, such as: freedom, stand alone, adventurer, hard work and persistent. In the novel is not seen about American culture but after it was transformed into movie of the American culture appeared which is freedom and adventurer which have been mentioned above.